In Vitro Assessment of Plants Growing in Cuba Belonging to Solanaceae Family Against Leishmania amazonensis. (2nd August 2016) - Monzote, Lianet; Jiménez, Jenny; Cuesta‐Rubio, Osmany; Márquez, Ingrid; Gutiérrez, Yamile; da Rocha, Cláudia Quintino; Marchi, Mary; Setzer, William N.; Vilegas, Wagner
Abstract : In this study, an in vitro antileishmanial assessment of plant extracts from 12 genera and 46 species growing in Cuba belonging to Solanaceae family was performed. A total of 226 extracts were screened against promastigotes of Leishmania amazonensis, and cytotoxicity of active extracts [median inhibitory concentration (IC50 ) promastigotes <100 µg/mL] was determined on peritoneal macrophage from BALB/c mice. Extracts that showed selective index >5 were then assayed against intracellular amastigote. Metabolomics analysis of promissory extracts was performed using chemical profile obtained by ultra performance liquid chromatography. Only 11 extracts (4.9%) from nine plants were selected as potentially actives: Brunfelsia cestroides A. Rich, Capsicum annuum L., Capsicum chinense Jacq., Cestrum nocturnum L., Nicotiana plumbaginifolia Viv., Solanum havanense Jacq., Solanum myriacanthum Dunal, Solanum nudum Dunal and Solanum seaforthianum And., with IC50 < 50 µg/mL and selectivity index >5 . Metabolomics analysis demonstrated significant differences in the chemical profiles with an average of 42.8 (range 31–88) compounds from m/z 104 to 1477, which demonstrated the complex mixture of compounds. In addition, no common markers among active extracts were identified. The results demonstrate the importance of the Solanaceae family to search new antileishmanial agents, particularly in unexplored species of this family. Copyright © 2016 John Wiley & Sons, Ltd.